Correlation between the Periapical Index and Lesion Volume in Cone-Beam Computed Tomography Images - Maia Filho, Etevaldo Matos; Calisto, Amanda Martins; Tavarez, Rudys Rodolfo de Jesus; Segato, Raquel Assed Bezerra; da Silva, Lea Assed Bezerra (Iranian Endodontic Journal, 2018)
Introduction: The study aimed to correlate the Periapical Index (PAI), obtained by way of periapical radiographs, with the volume of chronic periapical lesion, obtained through cone-beam computed tomography (CBCT), in the permanent teeth. Methods and Materials: Radiographs and CBCT images were selected from 35 single-rooted permanent teeth, with fully formed apices, with a diagnosis of pulp necrosis and chronic apical periodontitis that was radiographically visible. Two independent raters evaluated the radiographs on two separate occasions and classified the periapical lesions in accordance with Ørstavik’s PAI. The periapical lesion volume was calculated in the CBCT images. The correlation between the PAI and the lesion volume was calculated using Spearman’s correlation test. Results: There was a positive, moderate correlation between the PAI and the volume (rs=0.596; P<0.001) where rs2 is equal to 0.355, showing that only 35% of the PAI variation was dependent upon the variation in periapical lesion volume. Conclusion: The radiographic evaluation of the periapical lesion does not reflect the lesion’s volumetric characteristics as the volume had a moderate effect on the choice of PAI score. Keywords: Apical Periodontitis; Cone-Beam Computed Tomography; Endodontics; Periapical Radiography